If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 13 = 93 + -5x Reorder the terms: 13 + 5x = 93 + -5x Solving 13 + 5x = 93 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 13 + 5x + 5x = 93 + -5x + 5x Combine like terms: 5x + 5x = 10x 13 + 10x = 93 + -5x + 5x Combine like terms: -5x + 5x = 0 13 + 10x = 93 + 0 13 + 10x = 93 Add '-13' to each side of the equation. 13 + -13 + 10x = 93 + -13 Combine like terms: 13 + -13 = 0 0 + 10x = 93 + -13 10x = 93 + -13 Combine like terms: 93 + -13 = 80 10x = 80 Divide each side by '10'. x = 8 Simplifying x = 8
| 10+6x=30+x | | 5x-4=12x-60 | | 2x+36=11x-36 | | 2x+51=6x+11 | | 2x+21=6x+11 | | 2y+5=-9 | | 2y= | | 3x+5=166 | | 57+83= | | 5x+14=5x+24 | | -8p=88 | | (5v+2)(1+v)=0 | | 3d=57 | | -3y-8=11 | | 5x-2y=19 | | 0.35+0.24x=0.2(5-3x) | | 12x-11x-24=8 | | 5x-4x-10=13 | | 17y-2=88-y | | -3x-148+11x=84 | | -3x-9x^2= | | 1.5+3.8= | | 0.5x+0.2(3-2x)=0.04 | | 0.2x-0.3(5-2x)=0.4 | | 119-6x=12x+23 | | 8-9x=93-44x | | -87-9x=8x+15 | | 12x+9-5=11x-3 | | 5x+9=-63-7x | | -10-4x=8-10 | | 71-6x=8x+15 | | x^4-6x^2+9x=0 |